1986
DOI: 10.1021/ed063p42
|View full text |Cite
|
Sign up to set email alerts
|

The Curtin-Hammett principle and the Winstein-Holness equation: new definition and recent extensions to classical concepts

Abstract: One measure of value of a scientific principle is its frequency and scope of usage. Concepts are frequently developed for specific applications. It will be argued for the cases discussed herein, and perhaps more generally, that the original applications of a particular theory can serve unwittingly as an unfortunate limitation: the full development of the theory may be impeded if the theory is "locked into" its original application by a unidirectional mindset of potential users.The simplest kinetic system which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
0
6

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(149 citation statements)
references
References 20 publications
6
137
0
6
Order By: Relevance
“…Hence both linear and branched allylic esters can be used as starting materials to obtain the same protected b-hydroxy aldehydes. Reaction monitoring by 1 H NMR spectroscopy indicated that the Curtin-Hammett principle [47] applied in this case. The selectivity towards the branched aldehyde product resulted from the low rate at which the thermodynamically more stable linear allylic alcohol underwent oxidation and the relatively rapid palladium(II)-catalyzed interconversion between the branched and linear allylic alcohols.…”
Section: Anti-markovnikov Oxidations In Alcohols As the Solventmentioning
confidence: 85%
“…Hence both linear and branched allylic esters can be used as starting materials to obtain the same protected b-hydroxy aldehydes. Reaction monitoring by 1 H NMR spectroscopy indicated that the Curtin-Hammett principle [47] applied in this case. The selectivity towards the branched aldehyde product resulted from the low rate at which the thermodynamically more stable linear allylic alcohol underwent oxidation and the relatively rapid palladium(II)-catalyzed interconversion between the branched and linear allylic alcohols.…”
Section: Anti-markovnikov Oxidations In Alcohols As the Solventmentioning
confidence: 85%
“…Therefore, use of high temperature and long reaction time favor the formation of the thermodynamic product. Further details on thermodynamic and kinetic control and the Curtin-Hammet principle is available elsewhere [63][64][65].…”
Section: Reversible Competitive First-order Reactionsmentioning
confidence: 99%
“…The pseudoaxial and pseudoequatorial conformations of penicillin G bind with very similar geometries, but the energies of the two complexes differ by 2.73 kcal/mol. Since these are conformational isomers, the Curtin-Hammett principle applies (57), and only this energy difference is needed. It follows that the pseudoaxial conformation ofpenicillin G is bound preferentially to 17.…”
Section: Binding Of Penicillins To the Pbp Model 17mentioning
confidence: 99%